2017
DOI: 10.3847/1538-4357/aa5f5d
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Energy Distribution and Radio Halo of NGC 253 at Low Radio Frequencies

Abstract: We present new radio continuum observations of NGC253 from the Murchison Widefield Array at frequencies between 76 and 227 MHz. We model the broadband radio spectral energy distribution for the total flux density of NGC253 between 76 MHz and 11 GHz. The spectrum is best described as a sum of a central starburst and extended emission. The central component, corresponding to the inner 500 pc of the starburst region of the galaxy, is best modeled as an internally free-free absorbed synchrotron plasma, with a tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 81 publications
2
25
0
Order By: Relevance
“…With the full extents of disk and the halo of about 32 kpc along the plane and 14.5 kpc perpendicular to the plane, respectively, the halo-to-disk extent ratio at 146 MHz is ≈ 0.45. This is similar to the ratio for NGC 253 at 200 MHz (Kapińska et al 2017). However, we caution that the halo-to-disk extent ratio is strongly dependent on sensitivity and angular resolution; a better way to quantify the halo emission is via the scale height (see Section 8).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…With the full extents of disk and the halo of about 32 kpc along the plane and 14.5 kpc perpendicular to the plane, respectively, the halo-to-disk extent ratio at 146 MHz is ≈ 0.45. This is similar to the ratio for NGC 253 at 200 MHz (Kapińska et al 2017). However, we caution that the halo-to-disk extent ratio is strongly dependent on sensitivity and angular resolution; a better way to quantify the halo emission is via the scale height (see Section 8).…”
Section: Resultssupporting
confidence: 86%
“…Observations with the VLA at 330 MHz and 74 MHz suggested a flattening of the spectrum along the disk of the Milky Way (Kassim, private communication). Spectral turnovers due to free-free absorption have been observed in the integrated spectra of nearby starburst galaxies such M 82 at ≈ 500 MHz (Adebahr et al 2013), NGC 253 at 230 MHz (Kapińska et al 2017), and IC 10 at 322 MHz (Basu et al 2017). Spatially resolved free-free absorption has been observed in M 82 with Merlin at 408 MHz (Wills et al 1997) and with LOFAR at 154 MHz (Varenius et al 2015).…”
Section: Thermal Absorption In the Disk Of Ngc 891mentioning
confidence: 99%
“…Adebahr et al (2013) found a spectral turnover for the integrated spectrum of M 82 at 300 MHz, and even higher, at 600 MHz, for the starburst nucleus. Similarly, Kapińska et al (2017) found the 500 pc nuclear starburst region in NGC 253 best described by an internally free-free absorbed synchrotron spectrum with a turnover frequency of 230 MHz. Clearly, these two galaxies represent the more extreme cases in the local Universe and their starburst nuclei have SFR surface densities well in excess of 1 M yr −1 kpc −2 , hence are factor of 10 or higher than what is usually referred to as starburst galaxies.…”
Section: Introductionmentioning
confidence: 72%
“…Strong thermal absorption seems to be the only reasonable explanation for the distinct drop of low-frequency radio emission in the central part of M 82 (Wills et al 1997;Varenius et al 2015) and in other starburst galaxies (e.g. NGC 253 Kapińska et al 2017). Also, the turnovers found in the spectra of some regions in the centre of the Milky Way (Roy & Pramesh Rao 2006) are well accounted for by absorption effects.…”
Section: Discussionmentioning
confidence: 96%